An Analysis Of Efficiency And Effectiveness Of Regional Expenditure Bengkulu City In 2019-2022 - Depri Setiawan; Ahmad Soleh; Rina Trisna Yanti (Penerbit Jurnal Indonesia, 2023)
This research aims to determine the level of efficiency and effectiveness of regional expenditure Bengkulu City. This type of research is descriptive, a method that describes, compares and explains data so that conclusions can be drawn that are relevant to theory. The data used in this research is secondary data. The data collection method is the documentation method. Data obtained from agency websites, namely (BPS, DJPK KEMENKEU). The analysis results show that the average efficiency is 100%, this shows that the level of efficiency is still not efficient because the results are more than 80%. Effectiveness analysis shows that the calculation of the effectiveness of regional expenditure in 2019–2022 fluctuates with an average level of effectiveness of 88%, which means that the effectiveness of regional expenditure Bengkulu City is quite effective.